Metabolomics profile of two germinated maize flours (Atp-Y and Coca-sr) using gas chromatography-mass spectrometry (GC-MS) - Stephano Tambo Tene; Venkatachalapathy Natarajan (Exploration of Foods and Foodomics, 2025)
Aim: The germination of maize leads to many physiological changes in the plant. These changes are responsible for the appearance, disappearance, and variation in concentration of numerous compounds, including secondary metabolites. The aim of this study was to compare the secondary metabolite profile of two maize varieties germinated under controlled optimal conditions. Methods: To achieve this, the Atp-Y variety was soaked for 25.12 h at 25.54˚C in the presence of 0.5238% plant ash, germinated for 144.37 h, and matured for 37.65 h. For the Coca-sr variety, the grains were soaked for 1.608 h at 36.63˚C in the presence of 1.1093% plant ash. Germination and ripening took 144.37 h and 27.07 h, respectively. The compounds were extracted in methanol (HPLC grade) before being injected into a gas chromatography-mass spectrometry (GC-MS) equipped with an Rtx-5MS column for metabolite profiling. Results: These analyses showed that variety and optimum germination conditions influenced the secondary metabolite profile. This profiling identified 15 and 12 compounds in the Atp-Y and Coca-sr varieties, respectively. Of these compounds, 8 were identified in both varieties. The groups of compounds identified were fatty acids, esters, ketones, phenols, polyols, alcohols, sterols, and unclassified substances. Fatty acids were the most abundant, with proportions of 90.93% and 91.08% Atp-Y and Coca-sr, respectively. Within this group of compounds, (Z,Z)-9,12-octadecadienoic acid was the most abundant (46.58% for Atp-Y and 53.84% for Coca-sr), followed by (E)-9-octadecenoic acid (30.39% for Atp-Y and 25.09% for Coca-sr). 2-Methoxy-4-vinylphenol, a phenolic compound, was identified and quantified at 0.28% only in the Coca-sr variety, while the only polyol, 1,4-anhydro-D-mannitol, was identified in the Atp-Y variety. Conclusions: In view of these results, we would suggest using the Atp-Y variety to benefit from a wide range of compounds, but also to respect the malting conditions in order to benefit from the different compounds.